A Qualitative Survey on Psychological Experiences Among Malaysian COVID-19 Patients - Solehan, Hana Maizuliana; Mohamed, Nurul Azmawati; Mohd Rani, Mohd Dzulkhairi; Ithnin, Muslimah (International Journal of Human and Health Sciences (IJHHS), 2022)
Objectives: COVID-19 not only affects physical health, but also causes a significant impact on psychosocial wellbeing. Hence, it is important to understand the emotional and psychological experiences of COVID-19 patients. The objective of this study is to explore the psychological experience among the public when they were diagnosed with COVID-19. Methods. This cross-sectional study was done using a qualitative survey approach. The survey was conducted online via Google Form platform asking open-ended questions among patients diagnosed with COVID-19. The link to the online form was disseminated through social media and messaging applications from 1st March to 30th April 2021. Malaysian adult respondents with a history of positive COVID-19 were invited to share their experience, emotions and feelings dealing with the disease. The data was analysed using The Colaizzi method. Results. Ninety-five responses were received. Majority of the respondents were female (76.8%) with a median age of 35 years old. Four themes emerged from the qualitative analysis. The first theme was negative emotions experienced during early diagnosis of COVID-19 including denial, fear, guilt, stress, and depression. The second theme was the worry of other people, such as the stigma faced from others and concern regarding the family members’ health. The third theme was frustration and disappointment towards the health care system and then fourthly, positive emotions such as acceptance, good behaviour, and gratitude towards the health care staffs. Conclusion. COVID-19 imposed a great variety of emotional and psychological consequences. It is important to address a patient's psychosocial and emotional wellbeing for further support on coping mechanisms. Factors such as assistance from society, excellent care from the medical staffs and a good health-care system may ease their emotional burden. This study provides an understanding of negative and positive psychological impacts among COVID-19 patients in Malaysia. We found that negative emotions mainly occurred during the early COVID-19 diagnosis. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S36